2022
DOI: 10.1002/hyp.14667
|View full text |Cite
|
Sign up to set email alerts
|

Non‐linearity in event runoff generation in a small agricultural catchment

Abstract: Understanding the role of soil moisture and other controls in runoff generation is important for predicting runoff across scales. This paper aims to identify the degree of non‐linearity of the relationship between event peak runoff and potential controls for different runoff generation mechanisms in a small agricultural catchment. The study is set in the 66 ha Hydrological Open Air Laboratory, Austria, where discharge was measured at the catchment outlet and for 11 sub‐catchments or hillslopes with different r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Exner‐Kittridge et al (2016) also showed that the water of one of these downstream tile drainage systems chemically and dynamically originates from deep aquifers (Exner‐Kittridge et al, 2016). But some of these tile drainage systems, those that are located upstream, on the right side of the stream close to where the stream starts, are mostly ephemeral and they only get activated when the soils are saturated and the soil moisture state is high in the fields (Vreugdenhil et al, 2022). These upstream systems draining the agricultural fields together with the above listed factors promote large contributions of new water to runoff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exner‐Kittridge et al (2016) also showed that the water of one of these downstream tile drainage systems chemically and dynamically originates from deep aquifers (Exner‐Kittridge et al, 2016). But some of these tile drainage systems, those that are located upstream, on the right side of the stream close to where the stream starts, are mostly ephemeral and they only get activated when the soils are saturated and the soil moisture state is high in the fields (Vreugdenhil et al, 2022). These upstream systems draining the agricultural fields together with the above listed factors promote large contributions of new water to runoff.…”
Section: Discussionmentioning
confidence: 99%
“…These drains were installed in the 1950s, and we suspect that some of these clay pipes got broken over the years (Exner-Kittridge et al, 2016;Szeles et al, 2018). Furthermore, their outflow volumes are negligible or low compared to the volumes measured at the catchment outlet (Vreugdenhil et al, 2022). Most of these systems, those that are located on the left side of the stream downstream, have a considerable amount of subsurface runoff contribution demonstrated by diel fluctuations of their streamflow rates during rainless periods (Szeles et al, 2018) and by the fact that they do not fall dry through the whole year (Exner-Kittridge et al, 2016).…”
Section: Estimated New Water Fractionsmentioning
confidence: 99%
“…Although the sensitiveness of the catchment response to antecedent SWC conditions varies with soil properties and vegetation cover, it has been shown that including antecedent SWC in models improves runoff predictions (Castillo et al, 2003; Schoener & Stone, 2019; Zhang et al, 2011). Quite often, the influence of SWC on runoff generation in small catchments with contrasting climates revealed a threshold behaviour between antecedent SWC and both surface flow, such as stormflow volume, peak streamflow, runoff ratios (Farrick & Branfireun, 2014; Meyles et al, 2003; Vreugdenhil et al, 2022), and subsurface flow, such as pipe flow and shallow groundwater level (Penna et al, 2011; Tromp‐van Meerveld & McDonnell, 2006). This threshold behaviour is usually interpreted as a storage capacity deficit that must be filled and exceeded prior to triggering a significant streamflow response (Martínez‐Carreras et al, 2016).…”
Section: Introductionmentioning
confidence: 99%